Building Resilient Health Systems Experimental Evidence from Sierra Leone and the 2014 Ebola Outbreak - Christensen, Darin (World Bank E-Library Archive, 2020)
This paper experimentally examines efforts aimed at improving health worker performance in the context of the 2014-15 West African Ebola crisis. Roughly two years before the outbreak in Sierra Leone, the study randomly assigned two accountability interventions to government-run health clinics-one focused on community monitoring and the other gave status awards to clinic staff. The findings show that, prior to the Ebola crisis, both interventions led to improvements in utilization of clinics, patient satisfaction with the health system, and child health outcomes. During the crisis, the interventions led to higher reported Ebola cases, as well as lower mortality from Ebola, particularly in areas with community monitoring clinics. The paper explores the potential mechanisms, and the findings provide evidence consistent with the following mechanism: by building trust and confidence in health workers, and improving the perceived quality of care provided by clinics prior to the outbreak, the interventions encouraged patients to report and receive treatment. The results suggest that accountability interventions not only have the power to improve health systems during normal times, but also can make health systems resilient to crises that may emerge over the longer run